Model Tafsir Kontekstual Abdurrahman Wahid - Wildah Nurul Islami (MAGHZA, 2021)
Abdurrahman Wahid was a pioneer of the concept of religious moderation because his ideas included wasathiyyah (moderate) Islamic values. His transformative thinking tried to solve religious and national social problems with contextual interpretation of Quranic verses and gave rise to a model of moderate thinking that aligned with the principles of tolerance, brotherhood, and nationalism. His contextual interpretation generally uses the source of bi al Rayi interpretation, but his consistency cannot be ascertained because he never declared himself an interpreter. The method used is maudhui (thematic). There are several concepts of religious moderation taught by Wahid, including: 1. Pluralistic awareness in religion by removing the banning of religious understanding, 2. Awareness of the implementation of religious functions in social life to realize Islam rahmatan lil alamin, 3. The orientation of the nation is based on nationalism, not the formalism of religious teachings to realize ummatan wasathan, 4. The importance of interfaith dialogue to establish cooperation in social and muamalat, 5. Uphold the principles of justice (in human rights and economic ethics), professionalism, and tolerance, being patient, mature, forgiving and not authoritarian or demeaning to others.